Legal Consequences Of Husband's Infidelity To Legal Wife - Wulan Muharti, Catur (International Journal of Educational Research & Social Sciences, 2022)
Introduction, The legal consequences of husband's infidelity that occur in the household will have a negative impact on the wife and children.The infidelity committed by a husband greatly affects the psychology of his wife and children which results in the breakdown of the household. The rights of a wife who are threatened with not getting gono gini property if there is a marriage agreement. Marriage agreement before and after marriage. Problem formulation, 1)What is the legal protection for the wife if the husband is having an affair? 2) Will a wife who is a victim of infidelity get her rights if there is no marriage agreement? Normative juridical research method. Which includes legal principles, legal norms, and written and unwritten legal rules. The data collection method uses qualitative data analysis which aims to analyze the legal protection of infidelity, and dig deeper into the rights that will be obtained by a legal wife. The results of the study, 1) Written legal protection is not yet strong if there is no evidence. 2) The rights of a wife can be fought for by a court order.